2020
DOI: 10.1039/c9tc04984c
|View full text |Cite
|
Sign up to set email alerts
|

In situ investigation of perovskite solar cells’ efficiency and stability in a mimic stratospheric environment for high-altitude pseudo-satellites

Abstract: Perovskite solar cells with high power-per-weight have great potential to be used for aerospace applications such as satellites or high-altitude pseudo-satellites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…The temperature range required by American Institute of Aeronautics and Astronautics in their qualification testing [119] is −185 to 150 °C (88 to 423 K). This range exceeds that required by the IEC61215 terrestrial standard −40 to 85 °C, [41] and that used for testing perovskite cells for space application research to date: −85 to 20 °C, [56] and −193 to 27 °C. [59] Shi et al [118] recently showed that the presence of methyl ammonium (MA = CH 3 NH 3 ) in the cation component of the perovskite reduces their thermal stability while the presence of cesium (Cs) in the cation component is desirable reducing outgassing by five times.…”
Section: Thermal Stabilitymentioning
confidence: 78%
“…The temperature range required by American Institute of Aeronautics and Astronautics in their qualification testing [119] is −185 to 150 °C (88 to 423 K). This range exceeds that required by the IEC61215 terrestrial standard −40 to 85 °C, [41] and that used for testing perovskite cells for space application research to date: −85 to 20 °C, [56] and −193 to 27 °C. [59] Shi et al [118] recently showed that the presence of methyl ammonium (MA = CH 3 NH 3 ) in the cation component of the perovskite reduces their thermal stability while the presence of cesium (Cs) in the cation component is desirable reducing outgassing by five times.…”
Section: Thermal Stabilitymentioning
confidence: 78%
“…on top of the device would even further improve the lifetime stability, which remains to be our future study. [ 33–35 ] The high consistency of our device could be explained by the high air stability of the constituent materials (ZnO, PEDOT:PSS and F8BT).…”
Section: Resultsmentioning
confidence: 93%
“…5 Perovskite/CIGS tandem solar cells are currently optimized for terrestrial PVs and have shown rapid progress, 20,22 with recent demonstration of flexible perovskite/CIGS tandem solar cells, 54 thereby rendering the above outlook achievable. Promising results by Barbé et al 55 and Brown et al 56 further suggest that perovskite single-junction devices can tolerate extreme temperature changes and operate well under low-intensity and low-temperature environments, both of which can be found in some space environments, albeit this needs to be verified for perovskite/CIGS tandems and their more complex layer stack. Thermo-mechanical stress from temperature cycling, diurnal cycles, and/or partial shading can cause additional degradation pathways, conditions that are equally present in space, high-altitude, and terrestrial environments.…”
Section: Discussionmentioning
confidence: 99%